Hydroxylation at Multiple Positions Initiated the Biodegradation of Indeno[1,2,3-cd]Pyrene in Rhodococcus aetherivorans IcdP1 - Miao, Li-Li; Qu, Jie; Liu, Zhi-Pei (Frontiers in Microbiology, 2020)
Nowadays, contamination by polycyclic aromatic hydrocarbons (PAHs) has become a serious problem all over the world; in particular, high-molecular-weight PAHs (HWM PAHs, four to seven rings) are more harmful to human health and environment due to their more complex structure and metabolic pathway. Biodegradation of PAHs with six or more rings, such as indeno[1,2,3-cd]pyrene (IcdP), was rarely described. An IcdP-degrading strain, Rhodococcus aetherivorans IcdP1, was isolated from HWM PAH-contaminated soil. It could grow on and efficiently degrade various HWM PAHs, such as IcdP, benzo[a]pyrene, and benzo[j]fluoranthene. It showed highest degrading ability toward IcdP (> 70% within 10 days). The IcdP degradation was initiated by ring hydroxylation with multiple pathways, including the hydroxylation at the 1,2 and 7,8 positions, according to the relevant metabolites detected, e.g., cyclopenta[cd]pyrene-3,4-dicarboxylic acid and 2,3-dimethoxy-2,3-dihydrofluoranthene. The transcriptional patterns of the genes encoding ring-hydroxylating oxygenases (RHOs) and cytochrome P450 monooxygenases (CYP450s) under the induction of IcdP, pyrene, and benzo[b]fluoranthene (BbF) were compared to determine the key initial RHOs in the conversion of IcdP. The expression of genes encoding RHOs 1892–1894, 1917–1920, and 4740–4741 was induced strictly by IcdP, and the amino acid sequences of these proteins showed very low identities with their homologs. These results suggested that IcdP was degraded through a dioxygenation-initiated metabolism pattern, and RHOs 1892–1894, 1917–1920, and 4740–4741 responded to the initial ring cleavage of IcdP through 1,2-dihydrodiol or 7,8-dihydrodiol. The studies would contribute to the understanding of the molecular mechanism of initial degradation of IcdP.